The relationship between obsessive‐compulsive symptoms and PARKIN genotype: The CORE‐PD study. Issue 2 (12th November 2014) - Sharp, Madeleine E.; Caccappolo, Elise; Mejia‐Santana, Helen; Tang, Ming‐X.; Rosado, Llency; Orbe Reilly, Martha; Ruiz, Diana; Louis, Elan D.; Comella, Cynthia; Nance, Martha; Bressman, Susan; Scott, William K.; et al.
ABSTRACT Background Few studies have systematically investigated the association between PARKIN genotype and psychiatric co‐morbidities of Parkison's disease (PD). PARKIN‐associated PD is characterized by severe nigral dopaminergic neuronal loss, a finding that may have implications for behaviors rooted in dopaminergic circuits such as obsessive‐compulsive symptoms (OCS). Methods The Schedule of Compulsions and Obsessions Patient Inventory (SCOPI) was administered to 104 patients with early‐onset PD and 257 asymptomatic first‐degree relatives. Carriers of one and two PARKIN mutations were compared with noncarriers. Results Among patients, carriers scored lower than noncarriers in adjusted models (one‐mutation: 13.9 point difference, P = 0.03; two‐mutation: 24.1, P = 0.001), where lower scores indicate less OCS. Among asymptomatic relatives, a trend toward the opposite was seen: mutation carriers scored higher than noncarriers (one mutation, P = 0.05; two mutations, P = 0.13). Conclusions First, a significant association was found between PARKIN mutation status and obsessive‐compulsive symptom level in both PD and asymptomatic patients, suggesting that OCS might represent an early non‐motor dopamine‐dependent feature. Second, irrespective of disease status, heterozygotes were significantly different from noncarriers, suggesting that PARKIN heterozygosity may contribute to phenotype. © 2014 International Parkinson and Movement Disorder Society